Determination of Employee Performance Culture in the Perspective of Human Capital Management Its Impact on Services at Hospital - Nggilu, Ruqiah; Hamim, Udin; Puluhulawa, Jusdin (oneamd.com, 2025)
The purpose of this study was to determine and analyze the determination of employee performance culture and its impact on services at Aloei Saboe Gorontalo Hospital, including (a) competence. (b) management and (c) service incentives. This research method is a qualitative research type. The results of the study indicate: (1) the determination of employee competency development as human capital at the hospital is very possible because general practitioners and dentists are still dominant to be studied. Nursing staff and non-medical staff are still limited in quantity and quality. This limitation is not only in terms of quantity of manpower, but this limitation qualitatively still needs to be improved, both intellectual ability, performance, morals, attitudes, behavior, personality, and mindset as human capital in providing services, even though they have gone through